Non-Financial Compensation, Job Satisfaction, and Employee Performance at PT. Rum East Great Ternate - Rutsfi U. Lawarang; Adnan Rajak; Ruslan A. Kamis; Muhammad Asril Arilaha (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2023)
This study aims to determine and analyze the effect of non-financial compensation and job satisfaction on employee performance at PT. Rum East Great Ternate. The design in this study uses a quantitative approach by confirming previous research. The total sample of the study was 35 employees. Research data was collected through a survey with a questionnaire. Furthermore, for testing the research instrument, the questionnaire was tested through validity and reliability testing. The test tool used is multiple linear regression analysis. The results showed that non-financial compensation and job satisfaction had a positive and significant effect both partially and simultaneously on employee performance.